2022
DOI: 10.6007/ijarbss/v12-i10/15252
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Analysis of Published Literature on Repayment Behaviour in Microfinance

Abstract: This study identifies the main areas and current dynamics of repayment behaviour with regards to microfinance and suggests future research directions. We explored a selection of 258 papers from the Scopus database using bibliometric analysis to find research on repayment behaviour in terms of microfinance between 1996 and early 2022. Based on various citations and publications, as well as their location and relevance within the network, we identified the most influential articles and authors. We also analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In a study by Raza et al (2021), it was found that SMEs face financial constraints and lack of knowledge about sustainability issues. This finding is consistent with other studies that highlight the importance of support from external stakeholders, such as government agencies, industry associations, and NGOs (Hassan et al, 2022;Tong et al, 2022). Another important factor is the role of leadership in promoting sustainability in SMEs.…”
Section: Literature Reviewsupporting
confidence: 91%
“…In a study by Raza et al (2021), it was found that SMEs face financial constraints and lack of knowledge about sustainability issues. This finding is consistent with other studies that highlight the importance of support from external stakeholders, such as government agencies, industry associations, and NGOs (Hassan et al, 2022;Tong et al, 2022). Another important factor is the role of leadership in promoting sustainability in SMEs.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Figure 1. PRISMA Flow Diagram of The Search Strategy (source: Zakaria et al (2020) andHassan et al, (2022) …”
mentioning
confidence: 99%